Single-Frequency Linearly-Polarization Q-Switched Nanosecond Fiber Ring-Cavity Laser Enabled by an Electro-Optic Modulator - Siyu Chen; Dan Zhang; Wanru Zhang; Tao Wang; Can Li; Man Jiang; Jian Wu; Rongtao Su; Yanxing Ma (IEEE Photonics Journal)
We report a single-frequency linearly-polarized nanosecond fiber ring-cavity laser based on an electro-optic modulator. A 0.08-nm-bandwidth fiber Bragg grating combined with a section of 1-m unpumped Yb-doped fiber act as an ultra-narrow bandwidth filter to realize single-frequency laser output. The devices used in the experiments are all polarization-maintaining to ensure the linearly-polarized laser output. Pulsed laser is obtained by using electro-optic modulator to adjust the loss in the laser cavity periodically. And the repetition rate of pulse trains can be flexibly changed from 550 to 1000 kHz with a pulse width of 27–59 ns. By varying the amplitude of the arbitrary function generator, we obtained a single-frequency pulsed laser output with a pulse width of 51–493 ns. The linewidth of the laser is 31.8 MHz, and the polarization extinction ratio was better than 20 dB.